High incidence of AZF duplications in clan-structured Iranian populations detected through Y chromosome sequencing read depth analysis - Mogge Hajiesmaeil; Francesco Ravasini; Flavia Risi; Giorgia Magnarini; Anna Olivieri; Eugenia D’Atanasio; Hamid Galehdari; Beniamino Trombetta; Fulvio Cruciani (Scientific Reports, 2023)
Abstract The ampliconic region of the human Y chromosome consists of large duplicated sequences that can undergo non-allelic homologous recombination (NAHR), resulting in structural rearrangements that may cause infertility, especially when they occur in the azoospermia factor b/c (AZFb/c) region. Although AZF duplications have long been neglected due to the technical limitations of STS-based studies that focused mainly on deletions, recent next generation sequencing (NGS) technologies provided evidence for their importance in fertility. In this study, a NGS read depth approach was used to detect AZFb/c rearrangements in 87 Iranians from different ethnic groups. The duplication frequency in Iran proved to be twice as high as in the "1000 Genomes" dataset. Interestingly, most duplications were found in patrilineal ethnic groups, possibly as a consequence of their lower male effective population size which can counteract negative selection. Moreover, we found a large 8.0 Mb duplication, resulting in a fourfold increase in the copy number of AZFc genes, which to our knowledge is the largest duplication ever reported in this region. Overall, our results suggest that it is important to consider not only AZF deletions but also duplications to investigate the causes of male infertility, especially in patrilineal clan-based populations.